Quality of primary palliative care for older people with mild and severe dementia: an international mortality follow-back study using quality indicators. (8th June 2018) - Miranda, Rose; Penders, Yolanda W H; Smets, Tinne; Deliens, Luc; Miccinesi, Guido; Vega Alonso, Tomás; Moreels, Sarah; Van den Block, Lieve
Abstract: Background: measuring the quality of primary palliative care for older people with dementia in different countries is important to identify areas where improvements can be made. Objective: using quality indicators (QIs), we systematically investigated the overall quality of primary palliative care for older people with dementia in three different countries. Design/setting: a mortality follow-back survey through nation- and region-wide representative Sentinel Networks of General Practitioners (GPs) in Belgium, Italy and Spain. GPs registered all patient deaths in their practice. We applied a set of nine QIs developed through literature review and expert consensus. Subjects: patients aged 65 or older, who died non-suddenly with mild or severe dementia as judged by GPs ( n = 874). Results: findings showed significantly different QI scores between Belgium and Italy for regular pain measurement (mild dementia: BE = 44%, IT = 12%, SP = 50% | severe dementia: BE = 41%, IT = 9%, SP = 47%), acceptance of approaching death (mild: BE = 59%, IT = 48%, SP = 33% | severe: BE = 41%, IT = 21%, SP = 20%), patient–GP communication about illness (mild: BE = 42%, IT = 6%, SP = 20%) and involvement of specialised palliative services (mild: BE = 60%, IT = 20%, SP = 77%). The scores in Belgium differed from Italy and Spain for patient–GP communication about medical treatments (mild: BE = 34%, IT = 12%, SP = 4%) and repeated multidisciplinary consultations (mild: BE = 39%, IT = 5%, SP = 8% | severe: BE = 36%, IT = 10%, SP = 8%). The scores for relative-GP communication, patient death outside hospitals and bereavement counselling did not differ between countries. Conclusion: while the countries studied differed considerably in the overall quality of primary palliative care, they have similarities in room for improvement, in particular, pain measurement and prevention of avoidable hospitalisations.